PELATIHAN PEMBUATAN DAN PENGELOLAAN WEBSITE UNTUK TOKOH DAN REMAJA DI BLANG PULO LHOKSEUMAWE - Mutammimul Ula; Juniwan Ginting; Rosdiana Rosdiana; Mutmainnah Mutmainnah; Suriyanto Suriyanto (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
The community service activities of the community development scheme aimed to provide information technology skills through a training of website making and its management for village officials, leaders of Munawwarah mosque, and youth of Blang Pulo village. The problem that has been identified by the team was that there is no village website to explore village potential and promote Blang Pulo as well as increasing the economic level through promoting superior village products as the closest village to the Malikussaleh University campus. The methodology used in this community service activity encompassed: 1) site survey and village interview prior to conducting training and to identify problems; 2) provide an introduction to the website creation system and provide assistance in teaching community empowerment training materials; and 3) providing training materials for partners and village leaders, village apparatus and youth to provide website materials with wordpress. The purpose of this service included: 1) increasing the knowledge and abilities of village leaders and youth in making websites with WordPress; and 2) increasing the ability of village leaders and youth in operating and managing the website. The target of this community service activity was to empower community of Blang Pulo village in managing websites with Wordpress, explore village potential and promote village potential, providing up-to-date data information on village information websites, and increasing economic levels through the promotion of village superior products. The results of this service activity was the creation of village website and appointment of operator Blang Pulo village to manage the web and to set up all display menus properly and correctly. So, it was expected that the results of website management training are in accordance with the needs of the community and rural development goals.